Penerapan Teknologi Untuk Pengembangan Desa Wisata Cinunuk - Susetyaningsih, Adi; Sari, Mitha Mutia; Febriyanti, Tina; Ajhar, Alfi Nur; Mubarok, Encep Ahmad Husni; Wildan, Muhammad; Zakiyahi, Noviyanti Siti; Barokah, Putri Dara Lestari; Rachmat, Rio Adhitya; Nugraha, Akbar Dwinanda; Azhari, Audi Amhar; Gunadi, Musfik Alaida; Agustian, Zani; Yanuar, Syahrul; Rahayu, Yari Ardiansyah; Miraj, Ahmad Fauzi Saepul; Patria, Dhika Muhammad; Hantari, Anjas Ninda (Institut Teknologi Garut, 2022)
Tourism villages are an alternative to accommodate the needs of tourists where the potential of rural areas in the form of rural natural scenery, historical and cultural heritage as well as various folk arts and crafts have so far attracted the interest of tourists. Cinunuk Wanaraja Village, Garut Regency is considered to have various tourism potentials that can be an attraction, one of which is religious tourism and bathing tours in Cibolerang. If natural uniqueness or activities already exist in a village, then the next step is empowering the community to be involved in developing tourism potential in Cinunuk village, but this development has not run optimally because the potential of the village has not been maximally explored and there is still a lack of utilization of technology to support the tourism potential of Cinunuk. The method used is mixed methods including qualitative methods to examine aspects of supply, community characteristics and policies, quantitative methods to examine aspects of tourist interest and observation methods. With work programs that include improving environmental quality, industrial programs and the application of technology can solve problems faced by residents and can provide benefits in achieving increasing public awareness of environmental quality, increasing public knowledge of economic activities and increasing mastery of community information technology to support the development of tourist villages kiss.